Reducing the number of unnecessary routine laboratory tests through education of internal medicine residents. Issue 1118 (22nd January 2019) - Faisal, Annum; Andres, Kayla; Rind, Jubran Afzal Khan; Das, Aparna; Alter, David; Subramanian, Jeevarathna; Koehler, Tracy J; Parker, Jessica; Bernicchi, Nathan
Abstract: Introduction: The Choosing Wisely guidelines advise against ordering routine blood tests for hospitalised patients unless they change management. Unnecessary testing can lead to adverse effects (eg, iatrogenic anaemia, poor sleep quality, risk for infections and increased cost of care). Methods: An 8-week quality initiative aimed at reducing unnecessary blood tests was implemented in three internal medicine resident inpatient services. The initiative included a 30 min educational session, reminders prior to rotation and midrotation and posters in work areas that displayed lab pricing and urged judicious testing. Residents were encouraged to justify the purpose of ordering tests in their daily progress notes. Attending physicians were made aware of the initiative. Preintervention and postintervention time points were used to compare key metrics. A >10% decrease between time periods was used as an evaluation criterion. Results: There were 293 patient records reviewed in the preintervention period and 419 in the postintervention period. The two groups were similar in terms of age and gender. Median blood test count (complete blood count/basic metabolic profile/comprehensive metabolic profile) decreased from 4 to 2 tests per patient per day (50 % decrease) after the intervention. The median length of hospital stay decreased from 4.9 to 3.9 days (21% decrease). A decreased percentage of people requiring transfusions was also noted (2016: 6.1%, 2017: 2.9%). Conclusion: The frequency of unnecessary routine blood tests ordered in the hospital can be decreased by educating resident physicians, making them cost conscious and aware of the indications for ordering routine labs. Frequent reminders are needed to sustain the educational benefit.